The Politics of Clean Water Management: A Critical Review on the Scarcity of Clean Water in Kedungringin Village - Rahmawati, Restu; Firman, Firman (ARISTO, 2023)
This paper will examine the politics of clean water management, a review on the scarcity of clean water quality in Kedungringin Village, Sukawangi District, Bekasi Regency. This study is conducted due to a problem occurred in Kedungringin Village regarding the lack of access to clean water both in quality and quantity. Various efforts have been taken by the villagers of Kedungringin, such as constructing boreholes with the help of benefactors. However, this is insufficient to meet the needs of clean water for all residents. In this case, the role of PDAM Tirta Bhagasasi is limited as not being able to reach the Kedungringin Village area due to the far distance of Clean Water Pipeline from the location of Kedungringin Village. By these problems, this study will examine the efforts taken by PDAM Tirta Bhagasasi and the authority of Sukaringin Village in fulfilling the need of clean water access in Kedungringin Village. The research method used in this study is a descriptive qualitative research method with a case study approach. The results of this study indicate that the efforts taken by PDAM Tirta Bhagasasi in fulfilling the need of clean water for the villagers in Kedungringin have not been realized yet. This is for the reason thatin constructing a new clean water pipeline, PDAM Tirta Bhagasasi only reaches the housing/cluster area in Sukaringin Village. Hence, the clean water isunable to flow to Kedungringin Village since PDAM Tirta Bhagasasi prioritizes the cluster housing areas by collaborating with developers. This means that the well-financed community will be prioritized over the low-financed community.